Taṭbīqu Wasīlati Scrabble fī Istīʿābi al-Mufradāti al-Lughah al-ʿArabiyyah fī al-Madrasah al-Thānawiyyah al-Islāmiyyah al-Ḥukūmiyyah al-Khāmisah Jember: The Application of the Scrabble Method in Mastering Arabic Vocabulary at the Fifth State Islamic Senior High School (MAN 5) Jember - Nafisah, Ainun; Abicandara, Muh. Nidom Hamami; Sofiyanto, Irwan (Critical Review of English-Arabic World Journal, 2023)
يُعَدُّ تعلّمُ اللغة العربية أحدَ مقررات اللغات الأجنبية في المدارس، ولا يستطيع إلّا عددٌ قليل من الطلاب إتقانَها، سواء في مهارة الكتابة أو القراءة. وتتمثّلُ أبرزُ ضعفٍ لدى الطلاب عمومًا في قلّة المفردات، في حين أنَّ إتقان المفردات في تعلّم اللغة العربية يُعَدُّ أمرًا مهمًا لدعم الكفاءة اللغوية. لذلك، ولتسهيل تعلّم الطلاب وفهمهم للمفردات، تَتطلّب العملية التعليمية وجود وسيلة تساعد على تدريبهم وتعليمهم المفردات، ومن بين هذه الوسائل استخدام لعبة Scrabble. تُعَدُّ لعبة Scrabble وسيلة تُستخدم لتنمية المهارات اللغوية، ومنها مهارة إتقان المفردات. وللعبة Scrabble عدّة فوائد، من بينها زيادة الحصيلة اللغوية، لأنّ الطلاب يُطلَب منهم في هذه اللعبة ترتيبُ الحروف لتكوين المفردات، مما يساعدهم على تذكّر الكلمات بشكلٍ أفضل. هذا البحث هو بحثٌ وصفيّ ذو منهجٍ نوعي. وقد شملتْ عَيِّنَةُ البحث طلابَ الصف السابع (VII A) في مدرسة MTs Negeri 5 Jember. وتُظهِر نتائجُ البحث أن الوسائل التعليمية التي يستخدمها المعلّمون في تعليم اللغة العربية هي الكتب المدرسية وجهاز العرض (LCD). أمّا تطبيق وسيلة Scrabble فيتمّ من خلال تقسيم الطلاب إلى مجموعات عدّة، بحيث يحصل كلّ فريق على مجموعة من الحروف، ثم يطلب الباحث من الطلاب لصق الحروف على لوحة Scrabble التي أعدّها مسبقًا. وتُشير نتائجُ تطبيق وسيلة التعلّم باستخدام Scrabble إلى أن طلاب الصف VII A في MTs Negeri 5 Jember أصبحوا يمتلكون حصيلةً أكبر من المفردات، وتمكّنوا من زيادة عدد المفردات التي يعرفونها، كما أصبحوا قادرين على تذكّر المفردات بشكلٍ جيّد. Learning Arabic is one of the foreign language subjects at school and only a few students are able to master Arabic, even in written and reading form. The weakness of students in general is the lack of vocabulary. Meanwhile, mastery of vocabulary in learning Arabic is very important to support language proficiency. Therefore, to make it easier for students to learn and understand vocabulary, a medium is needed to train and teach the vocabulary, one of which is by using Scrabble. Scrabble is a medium used to develop language skills, one of which is vocabulary mastery. The Scrabble game has several benefits, one of which is increasing vocabulary because in this game students are required to arrange letters to form vocabulary so that students are able to remember vocabulary well. This research is descriptive qualitative research. The research objects were students in class VII A of MTs Negeri 5 Jember. The results of this research show that the media used by teachers in learning Arabic are textbooks and LCD. The implementation of Scrabble media is carried out by dividing students into several groups, each group gets a letter. Then the researcher instructed the students to stick the letters on the Scrabble board that had been prepared by the researcher. The results of the application of Scrabble learning media show that class VII A MTs Negeri 5 Jember masters more vocabulary and can increase their vocabulary and are able to remember vocabulary words well.